Case Report: Successful treatment of refractory synovitis, acne, pustulosis, hyperostosis, and osteitis syndrome and palmoplantar pustulosis with ustekinumab - Chen, Luxia; Liang, Qichang; Chen, Sijia; Cheng, Hao (Frontiers in Immunology, 2025)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a rare chronic inflammatory disease mainly manifested as skin and osteoarticular lesions. We describe a male patient with SAPHO syndrome who exhibited primary palmoplantar pustulosis (PPP). Notably, his condition worsened during treatment with adalimumab and other immunosuppressants. After switching to ustekinumab, the patient obtained significant improvement in both skin lesions and osteoarticular pain. These findings suggest that ustekinumab may represent an appropriate option for patients with refractory SAPHO syndrome.